Peran Human Capital dalam Meningkatkan Kinerja Perusahaan : Studi Literatur tentang Pengaruh Human Capital dan Budaya Organisasi Terhadap Kinerja Perusahaan - Ramadani, Gilang; Rizky, M. Chaerul (Universitas Pembangunan Panca Budi, 2024)
This study aims to examine the role of human capital in improving company performance with a focus on the influence of organizational culture. Human capital, which includes employees' knowledge, skills, and experience, is recognized as an important asset in creating competitive advantage. On the other hand, organizational culture serves as a framework that influences employees' behaviors and attitudes in achieving company goals. Through a comprehensive literature study, this article explores the relationship between human capital and organizational culture and its impact on firm performance. The results of the analysis show that strong human capital can increase employee innovation, productivity, and job satisfaction, which in turn contribute to the overall performance of the company. In addition, a positive and supportive organizational culture can strengthen the effectiveness of human capital by creating a work environment conducive to collaboration and learning. The study also identified several factors that influence the interaction between the two variables, such as leadership, internal communication, and human resource development policies. The conclusion of this study confirms the importance of integration between human capital and organizational culture in corporate management strategy. By understanding this relationship, companies can design more effective initiatives to improve their overall performance. The findings are expected to serve as a reference for practitioners and academics in developing policies that support the development of human capital and positive organizational culture.